Nonlinear Quadratic Programming Algorithm Modelling for Operation of The Off-Grid Energy Resources System with Backup Storage System - Abdeljelil Chammam; Pallathadka, Harikumar; Nada Qasim Mohammed; Shavan Askar; Naseer Ali Hussien; Saif Hameed Hlail (International Journal of Integrated Engineering, 2024)
This study aims to investigate and optimize the energy usage of multiple electrical systems operating off-grid. The focus is on maximizing the utilization of storage systems to ensure a reliable power supply. This is achieved by harnessing renewable energy sources such as backup storage systems, wind turbines, solar cells, and diesel generators. To meet the energy demand, both DC and AC loads on the consumer side are considered. The research employs a mathematical approach known as nonlinear quadratic programming to ascertain the most efficient energy generation for both producers and consumers. The primary aim is to minimize expenses the system. The study also evaluates the impact of battery storage systems on achieving the operational level. By analyzing the performance of these storage systems, the researchers can assess their contribution to the overall energy optimization. To validate the proposed optimization algorithm, the study implements it in Matlab software. This enables numerical simulations in various case studies of energy systems demonstrates the optimal energy generation and offers valuable insights into the performance of the proposed algorithm. Overall, this study contributes to the field of energy optimization in off-grid systems by considering multiple electrical systems, energy sources, and storage systems. The findings can help in designing and operating off-grid systems more efficiently, ensuring a reliable and cost-effective power supply.